Ammonites of the genera Peltoceras Waagen, 1871, Metapeltoceras Spath, 1931, and Euaspidoceras Spath, 1931 from the Upper Callovian and Oxfordian of Kachchh, western India, and their biostratigraphic potential - Pandey, Dhirendra Kumar; Alberti, Matthias; Fürsich, Franz (Journal of the Palaeontological Society of India, 2015)
Members of the family Aspidoceratidae Zittel, 1895 dominate the ammonite assemblage of the Upper Callovian of the Kachchh Basin. With the appearance of the genus Perisphinctes Waagen, 1869 in the Early Oxfordian they lose their dominance, but still form a relatively diverse group. In the present study, 32 ammonites from the Kachchh Basin in western India have been assigned to 18 taxa belonging to the genera Peltoceras Waagen, 1871, Metapeltoceras Spath, 1931, and Euaspidoceras Spath, 1931. Due to co-occurring ammonites as well as comparisons with European sections, most of these taxa can be attributed to ammonite zones of the Upper Callovian to lower Upper Oxfordian: Athleta Zone (Peltoceras kachhense, P. aff. kachhense, P. ponderosum, Metapeltoceras armiger, M. aff. armiger, M. cf. kumagunense, M flavum, Euaspidoceras acanthodes), Mariae-Cordatum zones (Euaspidoceras aff. babeanum), Cordatum Zone (Euaspidoceras waageni, E. simile, E. badiense), Cordatum-Transversarium zones (Euaspidoceras sparsispinum), PI icatilis-Bifurcatus zones (Euaspidoceras wagurense), and Bifurcatus Zone (Euaspidoceras varians, E. aff. jeanneti).
UnivIS-Import:2017-12-18:Pub.2015.nat.dgeo.IGM.LP.ammoni_5
Keywords: Ammonoids; taxonomy; biostratigraphy; Jurassic; Kachchh Basin; India